Posterior interhemispheric approach for surgical removal of a choroid plexus papilloma in the ventricular atrium. - Marcos Rodrigo Pereira Eismann (Brazilian Society for Pediatric Neurosurgery, 2020)
A 12 year-old boy with headaches for 2 months. Magnetic resonance imaging of the brain found a small lesion in the atrium of the right lateral ventricle. We show a posterior interhemispheric approach to the ventricular atrium through a corticotomy in the pre-cuneus and the posterior cingulate gyrus. This approach has the advantage of avoiding lesion to the optic radiation. A complete resection of the lesion was performed without complications. Anatomopathological result showed choroid plexus papilloma. This benign tumor corresponds to less than 1% of brain tumors and typically presents with signs of intracranial hypertension with hydrocephalus.